Operational risk mangement and implications for bank's economic capital - a case study - Radovan Chalupka; Petr Teplý (Charles University in Prague, Institute of Economic Studies (IES), 2008)
In this paper we review the actual operational data of an anonymous Central European Bank, using two approaches described in the literature: the loss distribution approach and the extreme value theory (EVT). Within the EVT analysis, two estimation methods were applied; the standard maximum likelihood estimation method and the probability weighted method (PWM). Our results proved a heavy-tailed pattern of operational risk data consistent with the results documented by other researchers in this field. Additionally, our research demonstrates that the PWM is quite consistent even when the data is limited since our results provide reasonable and consistent capital estimates. From a policy perspective, it should be noted that banks from emerging markets such as Central Europe are exposed to these operational risk events and that successful estimates of the likely distribution of these risk events can be derived from more mature markets.
Keywords: G18; G21; G32; 330; operational risk; economic capital; Basel II; extreme value theory; probability weighted method; Bank; Operationelles Risiko; Risikomanagement; Basler Akkord; Risikomaß; Kapitalstruktur